Kajian Karakteristik Marshall Dan Koefisien Kekuatan Relatif Lapis Hra (Hot Rolled Asphalt) Dengan Filler Fly Ash Menggunakan Agregat Kasar Sirtu Residu Galian C - Junaidi Junaidi (Politeknik Negeri Semarang, 2015)
Environmental problems such as pollution, destruction and disasters over the years is still ongoing and increasingly widespread. The condition not only causes environmental degradation but also a very serious impact on health and the human soul. Damage to the environment due to the soil / land also occurred in Waterford District C in the form of mineral mining (gravel). Mining is long overdue and is expanding. The existence of the mine excavation C has caused another problem in the form of accumulated waste material in gravel scattered around the place and the mining area. Starting from the above, it is necessary to think about how to take advantage of the rest of the mine rock gravel on aspalisasi activities. Step that needs to be done is to study the quality and characteristics of the asphalt mix by stacking materials using the gravel with reference to the specifications and requirements specified. This paper presents the results of research into the use of coarse aggregate gravel quarry C residue and fly ash filler in asphalt Hot Rolled Asphalt (HRA) in terms of the relative strength coefficients (a1) material in order to know the needs of pavement thickness HRA in the field.Coarse aggregate materials used in the study came from the residual quarry village C Munggangsari / Purbosari excl. Ngadirejo kab. Waterford, fly ash material derived from PT Jati Kencana Concrete (Ungaran) and AC 60/70 bitumen production Pertamina Cilacap. Equipment used for the study is the means test in the asphalt mixture Materials Laboratory of Civil Engineering Department Semarang State Polytechnic. Number of test specimens to be used in this study is 30 pieces and the test is done with reference to the SNI 06-2489-1990, including the value of stability, flow and MQ, density analysis and voids (VMA, VFWA, VITM). The study results showed that the residual gravel excavation C can be used as a mixture in which the HRA asphalt mix asphalt with gravel aggregate quarrying C has a value of stability between the above 744, the value of a1 between 0.28 to 0.38 which means it can support the traffic with heavy density. Based on the results of plotting the data parameters to the requirements of Highways marshall, obtained the optimum bitumen content of 7%. While based on a mixture of the three variations of rock and ash content of different fly ash show that the levels of HRA mixture with 100% filler stone dust showed the highest value a1. This shows that the addition of aditive fly ash as filler in the mix HRA HRA instead lowered pavement performance.